Negotiating caste, gendered and colonial subjectivities in the neoliberal academy - Dixit, Anukriti (My University, 2024)
This paper highlights how researchers are subjugated through hegemonic academic norms and how they simultaneously recognize the privileges attached to their subject positions. I illustrate difficulties in negotiating my privileges, particularly of caste, and my experiences of marginalisation as a ‘third world woman’ in the European academy. Such competitive insecurity is illustrative of both neoliberal logics of enterprise and responsibility as well as caste-based logics of merit and deservingness. Academia as a field of knowledge production historically consolidates power in the hands of a shrinking set of elites. Attitudes of competition and uncertainty produce subjects that turn to selfinterested modes of acquiring and analysing data, thereby producing hegemonic knowledges, which ignores the situatedness and politics of the research context. Caste is addressed together with gender, coloniality, ability, sexuality and ethnicity (among other subjectivities) as an intersectional co-producer of exclusion. Invoking caste-based imperialist logics is essential for unpacking the privileged subjectivities that produce elitism and exclusion in academia and in knowledge production.
Keywords: caste; Neoliberalismus; privilege; subjectivation; Wissenschaft; Wissensproduktion; ddc:300